2021
DOI: 10.1021/acs.jpclett.1c00233
|View full text |Cite
|
Sign up to set email alerts
|

A Hotspot’s Better Half: Non-Equilibrium Intra-Molecular Strain in Shock Physics

Abstract: Shockwave interactions with material microstructure localizes energy into hotspots, which act as nucleation sites for complex processes such as phase transformations and chemical reactions. To date, hotspots have been described via their temperature fields. Nonreactive, all-atom molecular dynamics simulations of shock-induced pore collapse in a molecular crystal show that more energy is localized as potential energy (PE) than can be inferred from the temperature field and that PE localization persists through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 68 publications
3
60
0
Order By: Relevance
“…To address this gap, we develop Many-Bodied Steered Molecular Dynamics (MB-SMD) in which we use four-body external biasing potential to deform molecular groups of interest along torsional and out-of-plane degrees of freedom. Four-body terms are motivated by our observation of the large molecular distortions observed under shock loading 35 as well as their general applicability to explore the conformational space of a molecule. This external biasing potential is implemented in the form of four-body harmonic inter-atomic potential, 𝐸 = 𝐾(𝜙 𝑖𝑗𝑘𝑙 − 𝜙 𝑜 ) 2…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address this gap, we develop Many-Bodied Steered Molecular Dynamics (MB-SMD) in which we use four-body external biasing potential to deform molecular groups of interest along torsional and out-of-plane degrees of freedom. Four-body terms are motivated by our observation of the large molecular distortions observed under shock loading 35 as well as their general applicability to explore the conformational space of a molecule. This external biasing potential is implemented in the form of four-body harmonic inter-atomic potential, 𝐸 = 𝐾(𝜙 𝑖𝑗𝑘𝑙 − 𝜙 𝑜 ) 2…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that a possible origin of this increased reactivity is the presence of highly strained and deformed molecules in the hotspot. 35,39 This energy localization, in the form of intra-molecular potential energy, is persistent well into reaction timescales. The increase in strain energy in TATB is caused primarily by torsional and out-of-plane deformations of the nitro and amino groups, shown in Section S5 of the SI, and incurs a local amorphization of the material that affects kinetics 59 and heat transport 60 .…”
Section: Role Of Many-body Strains In the Thermal Decomposition Of Tatbmentioning
confidence: 99%
See 2 more Smart Citations
“…Shock collapse of pores leads to even larger molecular-level strains than seen in shear bands. 57 These strained states were shown to persist across typical hot-spot reaction time scales and are postulated to give rise to a mechanochemical acceleration of decomposition kinetics.…”
Section: Introductionmentioning
confidence: 99%